Caracterização, avaliação antioxidante e citotóxica dos extratos da polpa e da casca de tucumã (Astrocaryum aculeatum) - Garcia, Luiz Filipe Machado (2012)
The identification of bioactive compounds in Brazilian fruit is extremely important for bioprospecting of natural substances with potential pharmacotherapeutic. Likewise, evaluations of profiles of antioxidant activity and toxicity are part of the initial processes of exploitation of plant extracts, being included in the efficacy and safety parameters. The Amazonian fruits have been noted for its excellent therapeutic potential in several experimental tests. Within this context is the tucumã, an Amazon fruit comes from a palm (Astrocaryum aculeatum), widely used in the state of Amazonas to the manufacture of candy, ice cream, liqueur or fresh consumption. Studies have shown the presence of a large amount of carotenoids in the fruit pulp. However, the fruit lacks information related to the antioxidant properties and presence of other chemical constituents. The objective of this study was to evaluate the ethanol extracts of the pulp and peel tucumã for the presence of bioactive compounds, antioxidant activity and cytotoxicity. The identification of bioactive compounds and total polyphenols were performed using High Performance Liquid Chromatography (HPLC) and Folin-Ciocalteau method, respectively. The antioxidants evaluations were made by the scavenger method of radical 2,2 - diphenyl-1-picril-hydrazyl (DPPH) and Total Reactive Antioxidant Potential (TRAP) test. The cytotoxicity assays were performed by the techniques of 3 - (4,5)-dimetiltialzolil difeniltetrazólio -2.5 (MTT) and by trypan blue exclusion. The results showed the presence of a large amount of polyphenols in the peel (790.9 ± 43.65 mg/100 g) and pulp (663.9 ± 92.40 mg/100 g) of the fruit. In addition, we detected the presence of important bioactive compounds such as flavonoids (peel = 77.9 ± 0.02 mg/100 g; pulp = 40.6 ± 0.06 mg/100 g), tannin (peel = 26.4 ± 0.01 mg/100 g; pulp = 6.4 ± 0.05 mg/100 g) and alkaloids (peel = 1.3 ± 0.29 mg/100 g; pulp = 0.7 ± 0.05 mg/100 g). Among the compounds identified were beta-carotene, rutin, quercetin, gallic acid, caffeic acid and chlorogenic acid, with higher concentrations in the peel in relation to the pulp (except the gallic acid). The extracts showed high antioxidant activity, with IC50 values corresponding to 8.98 ± 0.39 mg / ml (peel) and 11.24 ± 0.461 mg / ml (pulp) for the TRAP method, and 102.38 ± 4.8 ng / ml (peel) and 224.57 ± 3.9 (pulp) for the DPPH method. However, at concentrations above 100 μg / ml, both extracts showed cytotoxic effects. The results suggest that the ethanol extracts of the pulp and peel tucumã have high antioxidant activity in the presence of bioactive compounds that show great potential pharmacotherapeutic.